Determinants of unmet needs for healthcare and sexual health counselling among Ugandan university students with same-sex sexuality experience - Markus Larsson; Michael W. Ross; Gilbert Tumwine; Anette Agardh (Taylor & Francis Group, 2016)
Background: Research from sub-Saharan Africa has shown that persons with same-sex sexuality experience are at elevated risk for ill health due to sexual risk taking, stigma, and discrimination. However, studies of healthcare seeking among young people in this region with same-sex sexuality experience are limited. Objective: To identify determinants of unmet healthcare and sexual health counselling needs, respectively, among Ugandan university students with experience of same-sex sexuality. Design: In 2010, 1,954 Ugandan university students completed a questionnaire assessing socio-demographic factors, mental health, alcohol usage, sexual behaviours, and healthcare seeking. The study population consisted of those 570 who reported ever being in love with, sexually attracted to, sexually fantasised about, or sexually engaged with someone of the same sex. Results: Findings showed that 56% and 30% reported unmet healthcare and sexual health counselling needs, respectively. Unmet healthcare needs were associated with poor mental health and exposure to sexual coercion (OR 3.9, 95% confidence intervals [CI]: 2.7-5.7; OR 2.0, 95% CI: 1.3-3.0, respectively). Unmet sexual health counselling needs were significantly associated with poor mental health (OR 3.2, 95% CI: 2.1-4.8), exposure to sexual coercion (OR 2.6, 95% CI: 1.7-3.9), frequent heavy episodic drinking (OR 3.3, 95% CI: 1.9-5.8), and number of sexual partners (OR 1.9, 95% CI: 1.04-3.3). The associations between poor mental health, sexual coercion, and unmet healthcare needs (AOR 4.2, 95% CI: 2.1-8.5; AOR 2.8, 95% CI: 1.3-5.8) and unmet needs for sexual health counselling (AOR 3.3, 95% CI: 1.6-7.1; AOR 2.7, 95% CI: 1.4-5.4) persisted after adjustment for socio-demographic factors, number of sexual partners, and frequent heavy episodic drinking. Conclusions: These findings indicate that exposure to sexual coercion and poor mental health may influence healthcare seeking behaviours of same-sex sexuality experienced students. Targeted interventions that integrate mental health and trauma response are critical to meet the health needs of this population.